Role of the mitral valve in left ventricular assist device pathophysiology - Noly, Pierre-Emmanuel; Duggal, Neal; Jiang, Mulan; Nordsletten, David; Bonini, Mia; Lei, Ienglam; Ela, Ashraf Abou El; Haft, Jonathan W.; Pagani, Francis D.; Cascino, Thomas M.; Tang, Paul C. (Frontiers in Cardiovascular Medicine, 2022)
Functional mitral regurgitation (MR) in the setting of heart failure results from progressive dilatation of the left ventricle (LV) and mitral annulus. This leads to leaflet tethering with posterior displacement. Contrary to common assumptions, MR often does not resolve with LVAD decompression of the LV alone. The negative impact of significant (moderate-severe) mitral regurgitation in the LVAD setting is becoming better recognized in terms of its harmful effect on right heart function, pulmonary vascular resistance and hospital readmissions. However, controversies remain regarding the threshold for intervention and management. At present, there are no consensus indications for the repair of significant mitral regurgitation at the time of LVAD implantation due to the conflicting data regarding potential adverse effects of MR on clinical outcomes. In this review, we summarize the current understanding of MR pathophysiology in patients supported with LVAD and potential future management strategies.